A review of the bioelectrochemical system as an emerging versatile technology for reduction of antibiotic resistance genes. (November 2021) - Chen, Ping; Guo, Xiaoyan; Li, Shengnan; Li, Fengxiang
Graphical abstract: Highlights: The ARG generation and transmission mechanism are discussed in BESs. Less antibiotic pressure and less sludge help BESs reduce ARGs. Additives, antibiotic removal and microbial community affect ARG reduction in BESs. The coupling systems with BESs improve the original performance in reducing ARGs. Abstract: Antibiotic contamination and the resulting resistance genes have attracted worldwide attention because of the extensive overuse and abuse of antibiotics, which seriously affects the environment as well as human health. Bioelectrochemical system (BES), a potential avenue to be explored, can alleviate antibiotic pollution and reduce antibiotic resistance genes (ARGs). This review mainly focuses on analyzing the possible reasons for the good performance of ARG reduction by BESs and potential ways to improve its performance on the basis of revealing the generation and transmission of ARGs in BES. This system reduces ARGs through two pathways: (1) the contribution of BES to the low selection pressure of ARGs caused by the efficient removal of antibiotics, and (2) inhibition of ARG transmission caused by low sludge yield. To promote the reduction of ARGs, incorporating additives, improving the removal rate of antibiotics by adjusting the environmental conditions, and controlling the microbial community in BES are proposed. Furthermore, this review also provides an overview of bioelectrochemical coupling systems including the BES coupled with the Fenton system, BES coupled with constructed wetland, and BES coupled with photocatalysis, which demonstrates that this method is applicable in different situations and conditions and provides inspiration to improve these systems to control ARGs. Finally, the challenges and outlooks are addressed, which is constructive for the development of technologies for antibiotic and ARG contamination remediation and blocking risk migration.